Os efeitos do PAA e do PNAE na agricultura familiar da Região Administrativa de Paranavaí - Manfiolli, Marcelo Hussar (2014)
The current paper approaches the institutional markets of the Food Acquisition Program (FAP) and the School Food National Program (SFNP) - Acquisition of Foodstuffs of the Familiar Agriculture and the Rural Familiar Entrepreneur to School Food. We seek to evaluate how the programs are realized by the participants and how far the proposed goals by this public policy in the familiar agriculture in the administrative region of Paranavaí can reach. The study is focused on identifying the effects of this public policy in the familiar agriculture and in its organizations, and if this public policy leads to the straightening of the different forms of organization of the familiar agriculturists as informal groups, associations and cooperatives. The specific objectives were: a) infer if this public policy contributes to the development of the familiar agriculturists, their organizations, benefitting entities and community, identifying strategies so that the organization of familiar agriculturalists can gain strength, being able to access the institutional market, build an alternative and independent market; b) Analyze if the population in vulnerable and insecurity feeding situation, squared as consumers beneficiaries, are with their right guaranteed to a feeding according to their habits in the region of Paranavaí (counties of Querência do Norte, Paranavaí, Paranacity, Paraíso do Norte and Alto Paraná); c)comparatively to the Brazilian context, the occurred changes in the region of the study regarding the reversion of extreme misery conditions the increase of social indicators. The research started with the documents source collection in the executor organs of the FAP in the administrative region of Paranavaí, that is, the Regional Nucleo of the Work Secretary, Solidary Job and Economy (SETS), and also the executor organs of the SFNP, Regional Nucleo of Education (RNE), seeking to verify the number of implemented projects, value and benefitting public in the period from 2009 to 2013. The selected counties to the questionnaires application, based on the results of the FAP application in the years from 2009 to 2013, were: Alto Paraná, Paraíso do Norte, Paranacity, Paranavaí and Querência do Norte. The public policies FAP and SFNP have unanimous approval by the familiar agriculturists and they declare that in the hypotheses of interruption of these public policies there will be serious reflexes in the productive system. The contribution of the Public Policies of Food Acquisition to the development of the familiar agriculturists, of their formal organizations, benefitting entities, communities and counties is very significant. The familiar agriculturists have a raise, diversification and improvement of the income distribution during the year, guarantees from the market and commercialization, and the maintenance of the property in financial equilibrium and the families in the agriculture production. The familiar agriculturists' cooperatives can improve its organization structure, increase the profit and access new channels of commercialization. The benefitting entities have improvement of feeding habits and the food quality available to their consumers beneficiaries. The communities and counties have the greatest access to federal and state public policies resources, and the best income distribution among the poorest layers of population, the greatest financial circulation inside their range areas, the improvement of their social indicators and the decrease of population poverty.